Polarization Coupling of $X$ -Cut Thin Film Lithium Niobate Based Waveguides - Jingyi Wang; Pengxin Chen; Daoxin Dai; Liu Liu (IEEE Photonics Journal, 2020)
Thin film lithium niobate (LN) shows great potentials for highly compact passive and active devices. As LN is an anisotropic material, waveguides made on it exhibit different mode properties from those on conventional isotropic materials. We study the effective refractive indices of fundamental modes of two polarizations in etched ridge waveguides on an $X$ -cut LN thin film. Mode hybridization phenomenon, where the effective refractive indices of the two polarizations are close, is analyzed in detail with different structural parameters. Transmission through a 90° bend, which is a typical routing element for a photonic chip, is simulated. Significant polarization coupling related to the mode evaluation through the bend is observed, and becomes the dominant fact limiting the performance of this element. In order to ensure a low bending loss, the required bending radius is much larger than that for waveguides on an in-plane isotropic material, e.g. a $Z$ -cut LN thin film. Mode hybridization also plays an important role in the performance of the 90° bend, which should be avoided. Generally, decreasing the thickness of the LN thin film, working at a longer wavelength, or confining the propagation angle on a chip would help to decrease the polarization coupling.